Case Report: Is It Premature Ovarian Insufficiency or Swyer Syndrome After Bone Marrow Transplantation? - Li, Hui; Li, Jin; Li, Xiaohong; Yi, Hong; Ren, Qixiu; Chen, Xiaoyan (Frontiers in Pediatrics, 2022)
Introduction: Iatrogenic factor is one of the recognized causes for premature ovarian insufficiency. The aim of this case report was to present a rare case with premature ovarian insufficiency and 46, XY karyotype after bone marrow transplant (BMT) for thalassaemia major at childhood. We also reviewed some relevant literature in this report. Case presentation: A 17-year-old girl was presented with primary amenorrhea and premature ovarian insufficiency after receiving chemotherapy and BMT from her brother due to thalassaemia major at childhood. She had poor secondary sex characteristics, assessed as stage I for the development of breasts and external genitalia based on the Tanner scale. Transabdominal ultrasound showed small uterus with visible endometrial lining and small ovaries. Laboratory data showed hypergonadotropic hypogonadism profile with low level of estrogen and high level of follicular-stimulating hormone (FSH). Patient’s peripheral lymphocytes karyotype was 46, XY. Conclusions: This case was diagnosed as a chemotherapy induced premature ovarian insufficiency. Patient’s peripheral lymphocytes karyotype (46, XY) after she received BMT from a male donor was a misleading finding, and the case could be easily misdiagnosed as Swyer syndrome. A correct diagnosis in such cases should depend not only on the recent clinical findings, but also on the detailed medical history. To prevent premature ovarian insufficiency in similar cases, fertility preservation should be offered to girls before they receive chemotherapy, total body irradiation and BMT.